Factors Influencing the Level of Job Satisfaction of Lecturers at Universities in Providing Services and Improving Student Numeracy - Suwarni; Edy Saputra; Amândio de Araújo Sarmento; Tukiyo (LPPM Undiksha, 2025)
Factors influencing lecturers' job satisfaction in higher education, focusing on teaching practices and improving students' numeracy skills, have declined. The urgency of this research is critical, considering the challenges lecturers face in the 21st-century education era. This study aims to explore the relationship between self-efficacy, collaboration, stress, and lecturer job satisfaction. The method used in this study is a quantitative survey type with a population of active lecturers and students in Bengkulu, Indonesia, consisting of 980 respondents, including 160 lecturers and 820 students. Data was collected through a questionnaire designed to measure various variables related to teaching practices. Data analysis techniques include structural equation modeling analysis to identify relationships between variables. The study results indicate that self-efficacy and collaboration have a positive relationship with lecturer job satisfaction, while stress negatively impacts job satisfaction. The conclusion of this study emphasizes the need to create a collaborative work environment to support lecturer well-being, which will improve the quality of teaching and student learning experiences. Implications of this research include collaboration and support for lecturers to improve job satisfaction in higher education. The research implies that increasing lecturer job satisfaction contributes significantly to the quality of academic services and teaching effectiveness, especially in strengthening students' numeracy skills.